2016
DOI: 10.3748/wjg.v22.i4.1684
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus prevalence and genotype distribution in Pakistan: Comprehensive review of recent data

Abstract: Hepatitis C virus (HCV) is endemic in Pakistan and its burden is expected to increase in coming decades owing mainly to widespread use of unsafe medical procedures. The prevalence of HCV in Pakistan has previously been reviewed. However, the literature search conducted here revealed that at least 86 relevant studies have been produced since the publication of these systematic reviews. A revised updated analysis was therefore needed in order to integrate the fresh data. A systematic review of data published bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
145
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 92 publications
4
145
1
Order By: Relevance
“…Some researchers have noted that infection with HCV is higher in rural than urban areas [3,15]. Poverty has also been linked to the spread of common diseases [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers have noted that infection with HCV is higher in rural than urban areas [3,15]. Poverty has also been linked to the spread of common diseases [25].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis C virus (HCV) is a single stranded positive sense RNA virus of the Flaviviridae family [1][2][3]. This virus has a high level of sequence heterogeneity, but based on sequence homology, 6 major genotypes and many distinct subtypes have been identified [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, approximately 10 million people are suffering from HCV, the 6% of 6 . For the HCV percent in HD patients, as per the published literature and small sample size (ranging from 28-190) studies (n=6) results showed that the 26.02% of the haemodialysis patients is HCV infected and the rate of Prevalence become high in the past as compared to recent studies 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan is a resource constrains country with low per capita income and poor sanitary system. It ranked second in the world in term of HCV burden with more than 10 million infections [5,6]. Epidemiological data of HCV prevalence from last seven years (2010-2016) is reviewed and summarized in Figure 1.…”
mentioning
confidence: 99%